The Circular Restricted Three Body Problem(CR3BP) (Latakia University Journal -Basic Sciences Series, 2021)
interacting through Newtonian gravity. When the mass of one of the bodies is negligible compared to that of the other two bodies, the restricted three-body problem arises.The study and the theory of this problem has developed over the last 300 years. It is therefore,in this work we present a review of the problem and give a mathematical description of the general and restricted three body problem. In addition, we also present some simulation results which highlight the rich dynamics of the problem. At the end, we dealt with the problem of periodic orbits and equilibrium points (Lagrange) and zero velocity curves were illustrated using computer simulations (matlab) .Allof these would enrich our knowledge and deepen our understanding about the famous three-body problem as a whole.